2013
DOI: 10.3892/ol.2013.1406
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell migration by ouabain in the A549 human lung cancer cell line

Abstract: The Na+/K+-ATPase α subunit is highly expressed in malignant cells. Ouabain, a cardioactive glycoside, binds to the Na+/K+-ATPase α subunit and inhibits the activity of Na+/K+-ATPase. In the present study, the effect of ouabain on the migration of A549 cells was analyzed using the wound healing and transwell chamber migration assays. The impact of ouabain on the expression of E-cadherin, N-cadherin, vimentin, matrix metalloprotease (MMP)-2 and MMP-9 was also evaluated. Ouabain treatment not only inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
3
35
1
1
Order By: Relevance
“…The antimetastasis is one of the chemotheraptic function for anti‐cancer drugs . Numerous evidence have shown that ouabain also induced cytotoxic effects including induction of cancer cell apoptosis and inhibited cancer cell migration and invasion of human liver cancer A549 cells; however, there is no report to show ouabain inhibiting migration and invasion and altered associated gene expression in human bone cancer cells. Herein, we investigated the effects of ouabain on migration and invasion of human osteosarcoma U‐2 OS cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimetastasis is one of the chemotheraptic function for anti‐cancer drugs . Numerous evidence have shown that ouabain also induced cytotoxic effects including induction of cancer cell apoptosis and inhibited cancer cell migration and invasion of human liver cancer A549 cells; however, there is no report to show ouabain inhibiting migration and invasion and altered associated gene expression in human bone cancer cells. Herein, we investigated the effects of ouabain on migration and invasion of human osteosarcoma U‐2 OS cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain at physiological concentrations is able to inhibit the migratory activities of human lung cancer H292 cells . Ouabain inhibited the epidermal growth factor (EGF)‐enhanced migration of A549 cells and the basal migration of A549 cells in the absence of EGF . Ouabain inhibited cell migration in A549 cells appear to be related to its ability to regulate and inactivate Src‐to‐ezrin signaling …”
Section: Introductionmentioning
confidence: 99%
“…Thus, EGFR signaling mediates the initial stages of EMT and EGFR inhibition may restrain EMT in certain cellular contexts. In support of this hypothesis, ligand-independent, constitutively active forms of EGFR can increase motility and invasiveness of tumor cells and EGFR inhibitors block cancer cell migration in vitro (Liu et al , 2013; Yue et al , 2012)…”
Section: Hallmarks Of Transformationmentioning
confidence: 89%
“…A previous study reported that ouabain, a cardioactive glycoside, impedes invasion by decreasing the basal and enhanced migration in human lung cancer A549 cells 28 . Interestingly, it is observed that CK strongly inhibits the motility of lung cancer cells with or without EGF-stimulation ( Figure 5), suggesting that this might be an antimigratory activity of CK.…”
mentioning
confidence: 99%
“…Three hours later, each well was scratched using 10 l plastic pipette tip and washed with PBS. The medium was replaced with control medium or EGF-medium, following our treatment schedules (2% FBS, 2% FBS + EGF, 2% FBS + 50 M of CK, 2% FBS+ E GF + 50 M of CK) 28 . To quantify the scratched region, four randomly selected areas were photographed at  10 under an optical microscope (Eclipse ME600L, Nikon Instruments, NJ, USA).…”
mentioning
confidence: 99%